2010
DOI: 10.1164/rccm.201003-0335oc
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic Receptor Blockade Reverses Right Heart Remodeling and Dysfunction in Pulmonary Hypertensive Rats

Abstract: Adrenergic receptor blockade reverses RV remodeling and improves RV function in experimental pulmonary hypertension. Beta-adrenergic receptor blockers are not recommended in humans with PAH before their safety and efficacy are assessed in well-designed clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
214
5
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 264 publications
(244 citation statements)
references
References 56 publications
20
214
5
1
Order By: Relevance
“…We have reported that this right ventricle (RV) capillary rarefaction is associated with a decreased myocardial expression of VEGF-A. 35 Now we show that the expression of the VEGF-B splice variant [36][37][38] is likewise decreased in the tissues of failing rat RVs, further supporting the hypothesis that loss of expression of angiogenesis factors can explain the capillary rarefaction 35,39 in failing RVs. 34 …”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…We have reported that this right ventricle (RV) capillary rarefaction is associated with a decreased myocardial expression of VEGF-A. 35 Now we show that the expression of the VEGF-B splice variant [36][37][38] is likewise decreased in the tissues of failing rat RVs, further supporting the hypothesis that loss of expression of angiogenesis factors can explain the capillary rarefaction 35,39 in failing RVs. 34 …”
Section: Introductionsupporting
confidence: 60%
“…We found a significant reduction in the expressed VEGF-A protein, confirming previous results. 35 A new finding was a reduction in the expressed VEGF-B and VEGF-D proteins, which was not shared by the RV tissues obtained from chronically hypoxic rats, while the expression of VEGF-C trended toward a decrease in the RV tissue samples from SuHx rats without reaching statistical significance ( Fig. 2A-2E ).…”
Section: Survey Of Expressed Vegf Isoforms and Vegf Receptors In Lungmentioning
confidence: 84%
See 1 more Smart Citation
“…However, in the experimental setting there have been reports of drug-induced improvement of chronic RVF that did not affect the lung circulation. Bogaard et al 18 showed that treatment with the nonselective adrenergic receptor blocker carvedilol improved RV function and exercise tolerance. However, the exact mechanism whereby carvedilol treatment improved the function of the failing RV remains to be determined.…”
Section: The Lung Circulation-rv Axis: Implications For Future Therapiesmentioning
confidence: 99%
“…11 In addition, in PAH animal models β-blockers clearly have beneficial effects. [42][43][44] Why, then, has there not been an attempt to develop an antiadrenergic therapeutic strategy in PAH, where the status of the RV function is a major Figure 6. Chamber-specific norepinephrine (NE) and neuropeptide Y (NPY) depletion in failing right ventricles (RVs) from patients with pulmonary arterial hypertension (PAH).…”
Section: Could An Antiadrenergic Treatment Be Effective In Rvf Due Tomentioning
confidence: 99%